CSC662: Computer Security / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
The course will provide an overview of main problems and techniques of computer security. It will introduce the key security management issues, such as threats, attacks, objectives and measures. It will focus on technical security instruments deployed at various components of distributed systems, while keeping an eye on operational issues. Specific security mechanisms of common operating systems and network protocols will be covered. Exercises will contain "paper-and-pencil" problems for better understanding of theoretical fundamentals as well as some programming tasks.